Evidence of increasing functional differentiation in pottery use among Late Holocene maritime foragers in northern Japan. (June 2020) - Junno, Ari; Isaksson, Sven; Hirasawa, Yu; Kato, Hirofumi; Jordan, Peter D.
Abstract: Hamanaka 2 is a multi-phase coastal site in Rebun Island with a 3000-year occupation sequence extending from the final-stage Jōmon and Okhotsk to the Ainu Culture period (1050 BCE-1850 CE). To examine long-term trends in food processing at the site, we collected 66 ceramic sherds across six distinct cultural layers from the Final Jōmon to the Late Okhotsk period for lipid residue analysis. Given the site's beachfront location in an open bay, with ready access to abundant maritime resources, we predicted that the pottery would consistently have been used to process aquatic resources throughout all cultural periods. Though aquatic lipids dominated across the site sequence, the history of pottery use at the site proved more complex. Evidence of plant processing was found in all cultural phases, and from the Epi-Jōmon/Late Final Jōmon transition onwards 30% of the vessels were being used to process mixed dishes that combined both marine and terrestrial resources. By the start of the Okhotsk phase, separate sets of resources were being processed in different pots, suggesting functional differentiation in the use of pottery, and the rise of new kinds of cuisine – including the processing of millet. We tentatively explain these results as a consequence of the growing incorporation of Rebun Island into wider regional trade and interaction networks, which brought new kinds of resources and different social dynamics to Northern Hokkaido in the Late Holocene.